2007
DOI: 10.1592/phco.27.10.1394
|View full text |Cite
|
Sign up to set email alerts
|

Blood Management: A Primer for Clinicians

Abstract: and Introduction AbstractBlood transfusions are common in the hospital setting. Despite the large commitment of resources to the delivery of blood components, many clinicians have only a vague understanding of the complexities associated with blood management and transfusion therapy. The purpose of this primer is to broaden the awareness of health care practitioners in terms of the risks versus benefits of blood transfusions, their economics, and alternative treatments. By developing and implementing comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 142 publications
(189 reference statements)
0
46
0
3
Order By: Relevance
“…Control of bleeding in LPN, is an active area of investigation since uncontrolled hemorrhage negatively affects the mortality and morbidity rates, as well as the convalescence period. Traditional surgical methods including suture, energy based coagulation systems, ligature and hemostatic clips can be used to handle bleeding (12,13). Available hemostatic agents include absorbable hemostats such as gelatin, collagen and oxidized regenerated cellulose and active hemostats such as thrombin and fibrin sealants (16).…”
Section: Discussionmentioning
confidence: 99%
“…Control of bleeding in LPN, is an active area of investigation since uncontrolled hemorrhage negatively affects the mortality and morbidity rates, as well as the convalescence period. Traditional surgical methods including suture, energy based coagulation systems, ligature and hemostatic clips can be used to handle bleeding (12,13). Available hemostatic agents include absorbable hemostats such as gelatin, collagen and oxidized regenerated cellulose and active hemostats such as thrombin and fibrin sealants (16).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the morbidity, mortality, and extended hospitalization due to uncontrolled severe traumatic or surgical bleeding, the timely control of bleeding has obvious benefits for patients and for surgeons, and is an active area of research [11][12][13][14]. Surgeons encounter bleeding from a variety of tissue types, intensity, and etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Minimization of blood loss is important to help avoid hypovolemia, hemodynamic and metabolic deterioration, and anemia [13]. Minimization of exposure to blood component transfusion and the attendant risks has become increasingly important to patients and to surgeons [14]. Control of bleeding also facilitates surgeons' visualization of the surgical site, enabling precise and timely conduct of the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma transfusion is largely a safe procedure, a proportion of patients experience complications, which may be categorized as infectious or non-infectious complications [2]. Studies have shown a direct relationship between the amount of blood products that patients receive and the occurrence of serious complications [3]. Although the risk of viral transmission has been reduced since the implementation of donor screening for human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV), there is still a potential risk of acquiring viral infections when donors are undergoing seroconversion and can be infectious but not seropositive.…”
Section: Introductionmentioning
confidence: 99%
“…Although the implementation of transfusion safety measures has reduced the risks associated with transfusion, these are not completely effective and transfusion-related complications continue to present a healthcare burden [3]. Therefore the use of alternative plasma products with improved safety, which are also cost-effective, is becoming increasingly relevant in the effort to contain the economic impact of rising rates of plasma transfusions in the US.…”
Section: Introductionmentioning
confidence: 99%